2008
DOI: 10.1016/j.heares.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of human otosclerotic stapedial footplates

Abstract: Otosclerosis is a complex disease that results in a common form of conductive hearing loss due to impaired mobility of the stapes. Stapedial motion becomes compromised secondary to invasion of otosclerotic foci into the stapedio-vestibular joint. Although environmental factors and genetic causes have been implicated in this process, the pathogenesis of otosclerosis remains poorly understood. To identify molecular contributors to otosclerosis we completed a microarray study of otosclerotic stapedial footplates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…These were (i) a robust ‘naive pipeline’ based on retaining variants predicted to be deleterious by either PolyPhen-2 (20) or SIFT (21) and absent from dbSNP134; and (ii) a ‘candidate-gene pipeline’ where only variants in an otosclerosis candidate gene list of 494 genes were retained. The list included genes implicated in otosclerosis from association studies (22–26), gene expression studies (27), genes within linked regions of the genome (10–17,28) and genes known to be involved in other connective tissue disorders that can exhibit an otosclerosis-like hearing loss (29–33). The list also included 176 genes found to be differentially expressed in otosclerotic stapes by an RNA-seq analysis of 12 stapes (J.L.…”
Section: Resultsmentioning
confidence: 99%
“…These were (i) a robust ‘naive pipeline’ based on retaining variants predicted to be deleterious by either PolyPhen-2 (20) or SIFT (21) and absent from dbSNP134; and (ii) a ‘candidate-gene pipeline’ where only variants in an otosclerosis candidate gene list of 494 genes were retained. The list included genes implicated in otosclerosis from association studies (22–26), gene expression studies (27), genes within linked regions of the genome (10–17,28) and genes known to be involved in other connective tissue disorders that can exhibit an otosclerosis-like hearing loss (29–33). The list also included 176 genes found to be differentially expressed in otosclerotic stapes by an RNA-seq analysis of 12 stapes (J.L.…”
Section: Resultsmentioning
confidence: 99%
“…Although these loci have been mapped, we have little information regarding the role of these genes in disease development ( Table 2). While clinical similarities and some genetic association studies have suggested etiological relationship between otosclerosis and osteogenesis imperfecta, there is no evidence of a common genetic background in the two diseases [35,36]. Otosclerosis is rather considered as a complex bone remodeling disorder with relatively common monogenic forms [36].…”
Section: Otosclerosis (Otsc) Genes: Linkage Analysismentioning
confidence: 99%
“…Recently, microarray‐based gene expression profiling in human stapes tissue samples from OTSC cases and controls has shown the differential expression of two genes (PF4: upregulated, and IBSP: downregulated) playing roles in TGFB1 signaling . PF4 acts as an inhibitory protein that inhibits the binding of TGFB1 to type I receptors but not to type II receptors .…”
Section: Introductionmentioning
confidence: 99%